Confucian or confusion? Analyses of international students’ self-rated intercultural sensitivity and its sociocultural predictors at Canadian universities - Yuan, Xuechen (Frontiers in Education, 2023)
Introduction In mainstream psychological research, Confucian heritage culture is often the scapegoat for subjecting Confucian heritage culture students to cultural archetypes of reticence, obedience, and unassailability, leading to the stigmatization of international students. This study examines differences in international students’ self-rated intercultural sensitivity and the potential discrepancy that exists between large-scale differences in sociocultural dimensions and student perceptions of these dimensions. Methods A total of 120 international students enrolled at Canadian universities completed an online questionnaire which combines existing validated surveys on intercultural sensitivity and perceptions of sociocultural dimensions. Students were divided into two groups: Confucian and non-Confucian groups. The data analysis techniques include AN(C)OVAs, hierarchical linear regression, and Spearman’s rho correlation. Results The quantitative analyses lead to the main findings as follows: 1) Confucian heritage culture has little predictive value to intercultural sensitivity; 2) Confucian student group does not uniquely identify with Confucian values; 3) Second language apprehension, as the sole predictor, accounts for more variation in intercultural sensitivity than most sociocultural predictors combined. Discussion This study demonstrates that deterministic views of heritage culture may not accurately reflect international students’ personal identification with their heritage culture. Therefore, further research is needed to illuminate the role of studying abroad in deconstructing general culture and contextualizing students’ assumed fixed identities.